2017
DOI: 10.1161/hypertensionaha.117.09972
|View full text |Cite
|
Sign up to set email alerts
|

Labetalol Versus Nifedipine as Antihypertensive Treatment for Chronic Hypertension in Pregnancy

Abstract: maternal morbidity in these women (post hoc analysis). 10 The study highlights the need to determine which antihypertensive agent(s) provides optimal control of chronic hypertension in pregnancy to ameliorate these risks.Choice of antihypertensive outside pregnancy depends on ethnicity with those of African/Caribbean family origin receiving calcium channel blockers as first-line agent 11 and is thought to relate to differences in the pathophysiology causing hypertension in those of differing ethnic backgrounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 25 publications
2
44
0
1
Order By: Relevance
“…The primary results of the randomised controlled trial and the mechanistic comparison of antihypertensive treatment has been presented elsewhere. (48) This cohort study was reported in line with STROBE guidance for observational studies. (20)…”
Section: Methodsmentioning
confidence: 72%
“…The primary results of the randomised controlled trial and the mechanistic comparison of antihypertensive treatment has been presented elsewhere. (48) This cohort study was reported in line with STROBE guidance for observational studies. (20)…”
Section: Methodsmentioning
confidence: 72%
“…Meta-analysis and subsequent small trials have revealed no clear differences in maternal and perinatal outcomes. 24,[60][61][62] Compared with methyldopa, alternative drugs studied (ie, b-blockers and calcium channel blockers) may be more effective at reducing the risk of severe hypertension or preeclampsia. However, results for preeclampsia are inconsistent, and no firm conclusions can be drawn.…”
Section: Threshold For Treatment In Ongoingmentioning
confidence: 99%
“…Furthermore, ethnicity is an important confounder that we were unable to adjust for due to the limited numbers. A feasibility study has recently been completed that supports a larger RCT to compare the efficacy of different antihypertensive medications in the different ethnic groups [24]. Table 1.…”
Section: Discussionmentioning
confidence: 99%